Non-Fickian Absorption Characteristics of Adhesive Joints: Capillary Effects and Residual Properties - Johar, Mahzan; Wong, King Jye; Tamin, Mohd Nasir (International Journal of Integrated Engineering, 2018)
Mechanical performance of polymer-based adhesive joints is generally susceptible to moisture absorption. This study quantifies the effects of moisture content on the strength, stiffness, and energy properties of adhesive bonded joints. For this purpose, moisture absorption characteristics of structural adhesive joints (Araldite 2015) with different thicknesses (0.5, 1.0, and 1.5 mm) were firstly established under accelerated aging condition (deionized water at 60 oC). A thickness-dependent non-Fickian moisture absorption model was then used to characterize the moisture absorption of the adhesive joints. Results suggested that the moisture absorption of the adhesive joints was governed by the capillary action. Subsequently, adhesive joints with aluminum 6061 adherent and 0.5 mm-thick Araldite 2015 adhesive compound were subjected to dry, 0.1, 0.15, 0.18, and 0.2 pct of moisture content. The specimens were tested in shear and tension loadings at 1 mm/min. The resulting variations in the mechanical properties were fitted using a residual property model. It was noticed that all properties degraded upon moisture attack. For strength and energy properties, the degradation was more severe in tension. As for the stiffness, the decrease in the property was similar in both tensile and shear. The results from this study showed that moisture attack is an important aspect to be considered when designing for the service lifetime of adhesive bonded structures.